Measurement of Vibration on The Alternator Due to The Influence of Rotation Speed - Subekti Subekti; Hadi Pranoto; Muhammad Nurul Hidayat; Basuki Dwi Efendy (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2021)
The alternator or dynamo ampere is a device that functions as a generator that produces alternating current (AC) and converts it to direct current (DC). Signs of damage that often occur due to damage to the Alternator are the smell of burning, squeaking, dim spotlights, indicator lights, malfunction of the battery, and the supply of electricity. These signs will cause the vehicle to stop in the middle of the trip the electricity supply is very lacking. This requires that preventive maintenance checks on the alternator are a must in the automotive world. In this paper we research measuring the vibration of the alternator due to the influence of rotation speed (750 rpm and 1800 rpm), to predict damage to the alternator of the Daihatsu Luxio vehicle. The results of this study indicate that at the rotational speed of 750 rpm and 1800 rpm, were found 1x rpm the condition of the vibration amplitude on the alternator is smaller than the alternator in poor condition, this is due to the presence of an unbalanced alternator. Also, vibration due to misalignment is obtained because it has characteristics, among others: vibrations with a frequency of 1xRPM and/or accompanied by a relatively large 2xRPM, and relatively high vibration in the axial direction.